Avaliação dos sintomas psicológicos em pacientes pré e pós-transplante simultâneo pâncreas-rim. - Romano, Thais Malta [UNIFESP] (2018)
Introduction: The insulindependent diabetic patients associated with endstage renal disease (CRI) lead a life of intense suffering due to the dietary restrictions imposed by the incapacitating disease and chronic pain, and mainly by the dependence of the dialytic support. With the technical advances that have occurred in the last decade, simultaneous pancreaskidney transplantation (SPKT) has benefits for insulindependent diabetic patients with endstage renal disease. In addition to providing euglycemic status and normalization of renal function, SPKT has been shown to be important in the stabilization and even reversal of some chronic complications due to diabetes mellitus (DM), significantly improving the quality of life of these patients. The psychological aspects, especially anxiety and depression in simultaneous pancreaskidney transplantation and in chronic diseases in general are very frequent, leading to worsening of the evolution of both psychiatric and clinical disease. They may lead to low adherence to the therapeutic guidelines, in addition to greater morbidity and mortality. Psychic illnesses are often underdiagnosed and undertreated, mainly due to the presence of confounding clinical symptoms, which often occur in chronic diseases. Thus, the objective of this study was to establish and measure the most prevalent symptoms of depression and anxiety in patients with DM and with CRI waiting for SPKT, and to compare these symptoms with those found in patients already submitted to SPKT. Methods: Thirtyseven patients were studied, followed by the outpatient clinic of the Rim Hospital in São Paulo, 39 of whom were candidates for transplantation and in the waiting list, all patients with DM and CRI, and 88 patients who had undergone SPKT. Data from the Beck questionnaires were compared in the pre and post SPKT, which were divided into two groups: with symptoms anxiety/depression and no symptoms. Results: Significant differences were found between pre and post SPKT patients with regard to depression [18/39 (46.1%); 18/88 (20.4%); p = 0.003], respectively. Comparison of the symptoms of the BDI questionnaire between the groups revealed significant differences in relation to depression: feelings of punishment (p <0.001); suicidal thoughts (p = 0.008); irritation (p = 0.009); lack of energy / work / fatigue (p = 0.007); change in sleep pattern (p = 0.039); health concern (p = 0.004) and loss of interest by sex (p = 0.029). Regarding anxiety, there was no significant difference between the preand postSPKT groups [16/39 (41%); 25/88 (28.4%); p = 0.161)], respectively. However, the individual comparison of BAI items revealed significant differences in relation to anxiety: fear of the worst (p = 0.030); fear of dying (p = 0.005); frightening (p = 0.029); feeling of fainting (p = 0.015), all favoring posttransplantation. SPKT improves depressive symptoms both globally and specifically, and has a positive impact in terms of offering the patient greater interest and enthusiasm for life. Regarding anxiety, although there was no global improvement, SPKT seems to have a positive impact, offering greater feeling in relation to illness and life.